Female Religiosity in Self-Narration: Some Indicative Elements and Suggestions from Empirical Materials - Giorgia Pinelli (Religions)
This study stems from a collection of autobiographical narrations collected during a seminar held in February 2018 involving a small group of adults, representing the three major monotheistic religions: Catholicism, Judaism, and Islam. The seminar was organized by the University of Bologna (Department of Arts) in collaboration with the Association for Interreligious Dialogue “Abramo e Pace”. The aim of this paper is to re-examine the autobiographical narratives that emerged from the seminar, with a particular focus on the characteristics of female religious experiences in these religions, in order to identify distinctive trans-religious and transcultural signs. For this analysis, a sub-group of participants were selected, consisting of nine women, three Catholics, three Jews, and three Muslims, mainly between the ages of 35 and 45. The methodology used is a content analysis, which allows for a detailed examination of the narratives shared. From the narratives obtained, the religious education received in childhood and early adolescence emerges as a resource and support for the construction of personal identity regardless of the subsequent life paths taken by the individual. An additional pedagogical/educational theme of interest is represented by the intertwining of transformations of personal religiosity and dynamics of adult transformation, which is present in these narrations. Although the results do not aim for statistical representativeness, it is expected that the analysis will reveal certain constants that could inform subsequent, more systematic research efforts. In particular, it is expected that marriage, motherhood, and the education of children will emerge as moments of reactivation or revitalization of personal religiosity.